'Quilting' a play-based anti-bias curriculum for very young children: the Mosaic Approach. Issue 6 (2nd November 2022) - Kok, Xiu Wen; Yang, Weipeng
ABSTRACT: Anti-bias in early education is gaining importance, especially given the volatile social climate amidst the COVID-19 pandemic. Yet, Singapore preschools lack focus on anti-bias education despite being a multi-ethnic society. Set in the COVID-19 context, this teacher research developed and examined a curriculum to educate young children on anti-bias through play. The Mosaic Approach was adopted as the research methodology. Children's photography and drawing, interviews, child observations, and teacher journals were utilised to collect qualitative data for in-depth analysis. Evidence suggested that (1) supportive anti-bias curriculum and environment reflect authentic representations and active, developmentally appropriate involvement of all children, (2) anti-bias education is promoted through perspective-taking and reasoning in purposefully framed play-based experiences, and (3) anti-bias should permeate all areas of the preschool programme, including the physical classroom, curriculum, and teaching practices through collaborative efforts. This research also saw the Mosaic Approach's usability as an educational tool for anti-bias education. Other interpretations and implications of the results were discussed.